Simply this expression (-0.25x- 3) - (1.5x +1.4)

Skip to content# Simply this expression (-0.25x- 3) – (1.5x +1.4)

### Related Posts

##
This Post Has 3 Comments

### Leave a Reply Cancel reply

Home
Mathematics
Simply this expression (-0.25x- 3) – (1.5x +1.4)

Simply this expression (-0.25x- 3) - (1.5x +1.4)

The price decreased by 40 percent㏒㏒㏒㏒㏒㏒㏒㏒㏒㏒㏒㏒㏒∞㏒∞㏑⊕⊆⊂ф

SOLUTION:

= ( - 0.25x - 3 ) - ( 1.5x + 1.4 )

= - 0.25x - 3 - 1.5x - 1.4

= - 1.75x - 4.4

answer: x = 3 + √11 and x = 3 - √11

step-by-step explanation:

x² - 6x + 9 = 11

(x - 3)² = 11

x - 3 = ±√11

x = 3 ± √11

x = 3 + √11 and x = 3 - √11